2022
DOI: 10.1002/cssc.202200548
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Photocatalytic Aerobic Oxidation of Methane to Oxygenates with Water over W‐doped TiO2

Abstract: Highly selective conversion of methane to oxygenates with O 2 as a green oxidant remains a great challenge. It is still difficult to suppress the generation of CO x (x = 1, 2) as undesired byproducts due to unavoidable overoxidation reaction. Hence, tungsten-doped (W-doped) TiO 2 photocatalysts were designed with a tunable band structure for photocatalytic oxidation of methane to C 1 oxygenates using O 2 at low temperature (30 °C). The W-doping effectively modified the electronic and band structure of pristine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The lifetime of photogenerated carriers is usually as low as 10 –9 s while that for chemical reactions over the catalyst surface is in the range of 10 –8 –10 –3 s. ,, The charge recombination inevitably decreases the availability of the desirable photocatalytic activity. Many efforts have been devoted to prohibit the recombination of photogenerated carriers by electronic or band structure engineering, while metal doping and defect engineering provide two effective approaches to adjust carrier separation, transfer, and recombination. Metal doping and surface oxygen vacancies as electron traps can effectively inhibit the carrier recombination. Zhang et al showed that Cu-doped TiO 2 with abundant vacancies exhibited outstanding photocatalytic nitrogen fixation performance .…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime of photogenerated carriers is usually as low as 10 –9 s while that for chemical reactions over the catalyst surface is in the range of 10 –8 –10 –3 s. ,, The charge recombination inevitably decreases the availability of the desirable photocatalytic activity. Many efforts have been devoted to prohibit the recombination of photogenerated carriers by electronic or band structure engineering, while metal doping and defect engineering provide two effective approaches to adjust carrier separation, transfer, and recombination. Metal doping and surface oxygen vacancies as electron traps can effectively inhibit the carrier recombination. Zhang et al showed that Cu-doped TiO 2 with abundant vacancies exhibited outstanding photocatalytic nitrogen fixation performance .…”
Section: Introductionmentioning
confidence: 99%
“…For n-type semiconductors, the E fb is 0.1 eV more positive than the conduction band potential ( E CB ). 44 Therefore, the E CB of TiO 2 and CdS were discerned to be −0.40 and −0.79 eV ( vs. NHE), respectively. According to the formula of E VB = E CB + E g , the potential of the valence bands ( E VB ) of TiO 2 and CdS were determined to be 2.81 and 1.66 eV, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…For n-type semiconductors, the E  is 0.1 eV more positive than the conduction band potential (E CB ). 44 Therefore, the E CB of TiO 2 and CdS were discerned to be −0.40 and −0.79 eV (vs. NHE), respectively.…”
Section: Mechanism Analysismentioning
confidence: 92%
“…The characterization diffraction peaks at 27.7°, 30.0°, 33.2°, 45.2°, 47.6°, 51.8°, 55.9°, 57.2° and 72.8° were attributed to SWO (Figure S1) [12a] . As shown in Figure 1b, the pristine TiO 2 showed several vibration modes of 142 cm −1 (E g ), 397 cm −1 (B 1g ), 515 cm −1 (A 1g +B 1g ) and 636 cm −1 (E g ) [14] . The characteristic signals of SWO could be observed at 74, 102, 336, 799 and 921 cm −1 ascribed to B g (ν evt.…”
Section: Resultsmentioning
confidence: 94%